Perbandingan Ekstrak Bii Srikaya (Annona Squamosa) dengan Ekstrak Bii Kemiri (Aleurites moluccana) terhadap Daya Bunuh Kutu Rambut (Pediculus Humanus Capitis) (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Pediculus humanus capitis, according to the WHO, is classified as a skin disease and ectoparasite in the list of neglected tropical diseases. The cause can infect the scalp, leading to many children suffering from iron deficiency and anemia. Its spread occurs through shared items. Therefore, traditional insecticides such as srikaya seeds and kemiri seeds, which contain saponins and flavonoids capable of killing head lice, are required. The obective of this study is to determine the most effective concentration, compare their efficacy, and determine the killing time of both extracts. The experimental research method involved treatments at concentrations of 20%, 40%, and 60% with four repetitions. The results of this study indicate that there is an effect of srikaya seed extract with kemiri seeds in terms of concentration and time on lice mortality, as shown by a two-way ANOVA test with a p-value of 0.000 (P<0.05). In the Tukey test, the average mortality rate for srikaya seeds was 4, and the average mortality rate for kemiri seeds was 3. The concentration of srikaya seed extract killed 50% of head lice LC50 at a dose of 0,14%, while the concentration of kemiri seed extract killed 50% of head lice at a dose of 0,28% with contact times of 30 and 60 minutes. This demonstrates that srikaya seed extract at a dose of 0,14% is effective in causing mortality in head lice (Pediculus humanus capitis)